Economic Analysis of Solar PV System using Maximum Power Calculation of a Solar panel - Rama Vinay, A.Achuta; Chandan, K. Sri (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Solar panel maximum power is calculated with the equivalent circuit model in respect to the solar cell. Though different model circuits have been developed, basic practical circuit of a diode with ohmic losses is considered as the shunt resistance is very high and has a little influence in the model. The maximum power calculation is evaluated using mathematical methods and hence set to the further calculation of economic analysis of Solar PV system which includes Life cycle cost analysis, Cost benefit analysis and payback period helps to remain the objective of the paper.